2020
DOI: 10.1021/acsomega.9b04432
|View full text |Cite
|
Sign up to set email alerts
|

Global and Kinetic Profiles of Substrate Diffusion in Candida antarctica Lipase B: Molecular Dynamics with the Markov-State Model

Abstract: Profiling substrate diffusion pathways with kinetic information, which accounts for the dynamic nature of enzyme–substrate interaction, can enable molecular reengineering of enzymes and process optimization of enzymatic catalysis. Candida antarctica lipase B (CALB) is extensively used for producing various chemicals because of its rich catalytic mechanisms, broad substrate spectrum, thermal stability, and tolerance to organic solvents. In this study, an all-atom molecular dynamics (MD) combined with Markov-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The work also calls for further ITC studies on enzyme variants for fundamental studies to identify the involvement of positions of interest on reaction component binding or conversion . Finally, molecular modeling of the binding of reaction components can provide atomistic insights into binding processes. Because our approach is amenable to automation and scale-up for high-throughput, the combination of such diverse approaches will provide the high-quality data needed for the engineering of enzymes and biocatalytic processes through machine learning to speed up the future development of industrial biocatalysis. , …”
Section: Discussionmentioning
confidence: 99%
“…The work also calls for further ITC studies on enzyme variants for fundamental studies to identify the involvement of positions of interest on reaction component binding or conversion . Finally, molecular modeling of the binding of reaction components can provide atomistic insights into binding processes. Because our approach is amenable to automation and scale-up for high-throughput, the combination of such diverse approaches will provide the high-quality data needed for the engineering of enzymes and biocatalytic processes through machine learning to speed up the future development of industrial biocatalysis. , …”
Section: Discussionmentioning
confidence: 99%
“…59 Finally, molecular modelling of the binding of reactants can provide atomistic insight into binding processes. [60][61][62][63] Because our approach is amenable to automation and scale-up for high-throughput, the combination of such diverse approaches will provide the high-quality data needed for the engineering of enzymes and biocatalytic processes through machine learning to speed up the future development of industrial biocatalysis. 1,[64][65][66][67]…”
Section: Discussionmentioning
confidence: 99%
“…Another study using CMD simulation indicated that interfacial activation is due to a lamellar-like nanostructure formed by triglycerides (tricaproin and tricaprylin) in a water–triglycerides system . Furthermore, the role of the conformational dynamics of CALB during substrate binding was investigated by MD and the Markov state model (MSM) …”
Section: Introductionmentioning
confidence: 99%
“…24 Furthermore, the role of the conformational dynamics of CALB during substrate binding was investigated by MD and the Markov state model (MSM). 25 Improvements should be achieved by employing enhanced conformational sampling methods with explicit solvent models for the hydrophobic surface, followed by analysis of the freeenergy landscape concerning the lid open−close motion. In this regard, the combination of parallel cascade selection molecular dynamics (PaCS-MD), 27 an enhanced sampling method, and the Markov state model (MSM), 28−30 namely, PaCS-MD/MSM, can be used.…”
Section: ■ Introductionmentioning
confidence: 99%